Internet of Things (IoT) Enabled Green Surveillance System for Solar Site - Mohd Khusrin, Mohamad Afiq Afandi; Islam, Syed Zahurul (Evolution in Electrical and Electronic Engineering, 2023)
A surveillance system powered by solar energy and a lithium-ion battery pack is one of the systems that is very important nowadays. This system basically will be implemented in dark and dangerous areas with no source of electricity. Therefore, the prototype is designed to develop a surveillance system that consists of a camera and lamp that is powered by a PV panel and lithium-ion battery pack. Basically, the system will operate by using a full energy source from the sunlight through the PV panel. At the same time, the battery pack will be connected to the PV solar panel to store the electrical energy to provide a power supply when the PV solar panel does not generate enough electricity, especially during nights and cloudy days. The IP camera and DC lamp will act as loads where the IP camera has its own built-in Internet of Things (IoT) systems where it can be connected to the smartphone. The DC lamp can be controlled by using a smartphone through the Blynk application. The ESP8266 will act as a microcontroller to control the relay module that acts as a switch to open and close the power supply that passes through to the lamp. The system operated in 3 different types of weather which are during normal days, cloudy days, and rainy days. The results show that during a normal day, the amount of electricity produced from the PV solar panel is the highest compared to a cloudy and rainy day. Besides, the lithium-ion battery pack also can store extra energy which can be used to supply electricity efficiently, especially during the autonomous day. With sufficient energy sources, the IP camera can function very well where it can record and store data 24/7 while the LED lamp can be turned on at night and turned off during daylight.